Caribbean Report 18-09-1995 - Orr, Carol (anchor); Barnhill, Bobbie (correspondent); Wildman, Sherman (interviewee); Coughlan, Geraldine (correspondent); Hartley, David (interviewee); Campbell, Parnell (interviewee); Williams, Colin (correspondent); Ninvalle, Pete (correspondent); Mitchell, James (interviewee); Osana, Roy (correspondent); Ransome, Debbie (correspondent); McDonald, Trevor (interviewee); et al. (The British Broadcasting Corporation, 1995)
In this report the US Virgin Islands are described as a war zone after the passage of hurricane Marilyn. The hurricane bypassed Puerto Rico but the islands of Vieques and Culebra, south of the mainland, suffered considerable damage. Meanwhile, in Britain Caribbean communities rally around their home countries following the damages done by both hurricanes. However, they felt that the British government could be doing more in aid relief for the Caribbean. Foreign Office spokesman David Hartley comments that disaster relief for all the Caribbean is placing a strain on Britain's Overseas Development Administration. In St. Vincent and the Grenadines, the Attorney General Parnell Campbell announced his intention to step down from office by month's end following allegations of financial impropriety. Prime Minister James Mitchell states that Campbell's resignation raises wider concerns such as proper salaries for professionals in government. In Washington, Colin Powell, former US Chairman of Joint Chiefs of Staff, launched his autobiography amid speculation about his next step towards the Presidential chair. In London, a book on the history of black press in Britain was launched. Trevor McDonald wrote the foreword for the book and stated that there continues to be a niche for black media in Britain.
1. Headlines with Carol Orr (00:00-00:31)
2. The US Virgin Islands described as a war zone after damage caused by hurricane Marilyn (00:32-02:59)
3. Hurricane Marilyn bypasses mainland Puerto Rico but causes considerable damage to the islands south of Puerto Rico (03:00-04:05)
4. The British government accused of not doing enough for aid relief for the Caribbean after both hurricanes (04:06-06:09)
Keywords: Hurricane damage -- Virgin Islands of the United States; Hurricane damage -- Puerto Rico; Disaster relief -- Virgin Islands of the United States; Emergency management -- Caribbean Area; Disaster relief -- Caribbean Area; Humanitarian assistance -- Caribbean Area; Economic assistance, British -- Caribbean Area; Politicians -- Saint Vincent and the Grenadines; Political corruption -- Saint Vincent and the Grenadines; Public officers -- Resignation -- Saint Vincent and the Grenadines; Professional employees -- Salaries, etc. -- Saint Vincent and the Grenadines; Autobiography; Statesmen -- United States -- Biography; African American generals -- Biography; Blacks -- Great Britain; Mass media and race relations -- Great Britain; British newspapers -- History